DAMPAK KECERDASAN BUATAN TERHADAP PERKEMBANGAN BAHASA MANUSIA DAN BAHASA HEWAN - Thania Aprilia; Ziska Oktanesa; Silvina Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article examines the impact of Artificial Intelligence (AI) on the development of human language as well as its contribution to understanding communication systems in animals. Advances in digital technology enable AI to influence the use and acquisition of human language while also opening new opportunities for analyzing animal vocalizations such as those of dolphins, birds, and primates. This study employs a qualitative descriptive method based on a literature review that analyzes various linguistic theories, AI-related research, and studies on animal communication. The findings indicate that AI accelerates linguistic changes in humans and simultaneously enhances scientific capability in mapping patterns of animal communication. However, AI also presents challenges, including the homogenization of language and the risk of misinterpreting animal communication. In conclusion, AI serves as a major agent of change that facilitates the evolution of human language and broadens our understanding of animal communication.